2018
DOI: 10.1186/s13023-018-0921-4
|View full text |Cite
|
Sign up to set email alerts
|

Economic impact of screening for X-linked Adrenoleukodystrophy within a newborn blood spot screening programme

Abstract: BackgroundA decision tree model was built to estimate the economic impact of introducing screening for X-linked adrenoleukodystrophy (X-ALD) into an existing tandem mass spectrometry based newborn screening programme. The model was based upon the UK National Health Service (NHS) Newborn Blood Spot Screening Programme and a public service perspective was used with a lifetime horizon. The model structure and parameterisation were based upon literature reviews and expert clinical judgment. Outcomes included healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…A well-defined process for both population and targeted screening exists. Examples of recent costing studies informing the process of the addition of screening conditions include studies on the economic impact of adding ALD [ 1070 ], the cost effectiveness of adding SCID [ 1071 ], and re-examination of the cost effectiveness adding five conditions (GA-I, HCY, IVA, LCHAD, and MSUD) [ 1072 ]. A costing analysis of teleconsultations as a means of communicating positive screening results was recently reported [ 1073 ] along with an in-depth description of the communication project and its collaborators (laboratory staff, clinicians communicating positive screening results, and parents) [ 1074 ].…”
Section: Resultsmentioning
confidence: 99%
“…A well-defined process for both population and targeted screening exists. Examples of recent costing studies informing the process of the addition of screening conditions include studies on the economic impact of adding ALD [ 1070 ], the cost effectiveness of adding SCID [ 1071 ], and re-examination of the cost effectiveness adding five conditions (GA-I, HCY, IVA, LCHAD, and MSUD) [ 1072 ]. A costing analysis of teleconsultations as a means of communicating positive screening results was recently reported [ 1073 ] along with an in-depth description of the communication project and its collaborators (laboratory staff, clinicians communicating positive screening results, and parents) [ 1074 ].…”
Section: Resultsmentioning
confidence: 99%
“…After duplicate removals, 716 articles were considered eligible for screening by title and abstract. After full-text screening, 35 articles were included for the final assessment (see Appendix C for the PRISMA flow diagram) [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ]. No additional studies were found on the websites of the INAHTA HTA agencies.…”
Section: Resultsmentioning
confidence: 99%
“…In their EE on a panel of screening for metabolic disorders, Thiboonboon et al included a budget impact analysis to estimate resource impact over a 10-year interval [ 30 ]. An expected value of perfect information analysis was additionally undertaken by Bessey et al [ 44 ], who calculated the value of eliminating all uncertainty in the model parameters.…”
Section: Resultsmentioning
confidence: 99%
“…Economic evaluation A process of systematic identification, measurement and valuation of the inputs and outcomes of two alternative activities, and the subsequent comparative analysis of these Grosse et al (2016); Prosser et al (2013); Wright et al (2015) Programmatic cost analysis A process to compare the program costs to program outcomes which can include all the resources required to implement an intervention, including personnel, space and utilities, travel, materials, and supplies Bessey et al (2018) Cost-effectiveness analysis A process that examines both the costs and health outcomes of one or more interventions and compares an intervention to another intervention (or the status quo) by estimating how much it costs to gain a unit of a health outcome, such as a life year gained, or a death prevented Castilla-Rodríguez et al ( 2017); Chan et al (2011); Kemper and Downs, (2000) Cost of illness analysis A method of measuring medical and other costs resulting from a specific disease or condition Tran et al (2007) Cost-benefit analysis A systematic approach where the program costs and benefits are converted into dollars to estimate the strengths and weaknesses of alternatives used to determine options which provide the best approach to achieving benefits while preserving savings Ding et al (2016); Khneisser et al (2015); Lord et al (1999) Cost-utility analysis A special type of cost-effectiveness analysis which includes health outcomes in the analysis (such as quality adjusted life year (QALYs)) Carroll and Downs, (2006) Budget Impact analysis (also called 'business case analysis)…”
Section: Type Of Analysis Description Referencesmentioning
confidence: 99%